1997
DOI: 10.1002/(sici)1099-0798(199724)15:1<95::aid-bsl255>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Law School Performance Predicted by Explanatory Style

Abstract: The explanatory styles of 387 law students were assessed prior to law school using the Attributional Style Questionnaire (ASQ). Longitudinal performance measures were collected throughout law school and related to each student's initial explanatory style. In contrast to studies with undergraduates, students who made stable, global, and internal attributions for negative events combined with the converse attributions for success (typically called pessimists) outperformed more optimistic students on measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
(6 reference statements)
0
24
0
2
Order By: Relevance
“…But they are useful for predicting successful adaptation in broad domains of activity, where it is generally found that people with an optimistic explanatory style or an internal locus of control do better than others (Scheier & Carver, 1985;Seligman, 1991). There are, however, a number of exceptions to this rule, and there appear to be situations in which externality and pessimism are adaptive, such as, perhaps, law school (Satterfield, Monahan, & Seligman, 1997). Generalized control beliefs are particularly useful in new situations and contexts, where domain-specific self-knowledge may not be available.…”
Section: Construct 4: Generalized Control Beliefsmentioning
confidence: 99%
“…But they are useful for predicting successful adaptation in broad domains of activity, where it is generally found that people with an optimistic explanatory style or an internal locus of control do better than others (Scheier & Carver, 1985;Seligman, 1991). There are, however, a number of exceptions to this rule, and there appear to be situations in which externality and pessimism are adaptive, such as, perhaps, law school (Satterfield, Monahan, & Seligman, 1997). Generalized control beliefs are particularly useful in new situations and contexts, where domain-specific self-knowledge may not be available.…”
Section: Construct 4: Generalized Control Beliefsmentioning
confidence: 99%
“…Houston (1994) found that students who perform well make stable and, to some extent, global attributions. Satterfield et al (1997) demonstrated that law students with pessimistic explanatory style (consisting of stable, internal, and global attributions for negative events) had a higher GPA than law students with optimistic explanatory style. Further, Bridges (2001) indicated that SAT, but not attributional style, was significantly related to later performance on course-related objective exams in college.…”
Section: Discussionmentioning
confidence: 99%
“…These students tend to be passive when they encounter obstacles and eventually give up (Peterson & Barrett, 1987). Yet, it must be noted that the relationship between attributional style and GPA seems to be moderated by different variables such as students' ability level (Gibb, Zhu, Alloy, & Abramson, 2002;Houston, 1994), major (Satterfield, Monahan, & Seligman, 1997), and time of the semester (Yee, Pierce, Ptacek, & Modzelesky, 2003). IN PSYCHOLOGY (VOL.…”
Section: Optimism and College Gradesmentioning
confidence: 99%
“…In some studies a pessimistic explanatory has been associated with better academic performance than an optimistic explanatory style (e.g., Houston, 1994;LaForge & Cantrell, 2003;Satterfield et al, 1997).…”
Section: Person Stimulus (Entity) Situationmentioning
confidence: 96%
“…The purpose was to understand when and why pessimistic explanatory style is associated with higher academic achievement. Satterfield, Monahan, and Seligman (1997) suggested some possible explanations for this when they found results in the anomalous direction. The possible use of the strategy of defensive pessimism by their population was one of these suggested explanations.…”
Section: Introductionmentioning
confidence: 99%